Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Produk Agribisnis UMKM - Surya Sevi Wijayanna Lumban Tobing; Zainal Zainal (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Consumer purchase decisions are a critical factor in the sustainability of agribusiness micro, small, and medium enterprises (MSMEs), particularly in rural areas. This study aims to analyze the effect of X1 and X2 on purchase decisions of agribusiness MSME products in Tanjung Anom Village, Pancur Batu District, Deli Serdang Regency. This research employed a quantitative approach using a survey method. Data were collected from 300 respondents selected through purposive sampling. The research instrument was a questionnaire measured on a five-point Likert scale, and the data were analyzed using multiple linear regression. The results indicate that X1 and X2 simultaneously have a significant effect on purchase decisions, with significance values below 0.05. Partially, both X1 and X2 have positive and significant effects on purchase decisions, with X1 identified as the most dominant variable. The Adjusted R Square value of 0.578 indicates that 57.8% of the variance in purchase decisions can be explained by X1 and X2, while the remaining variance is influenced by other factors outside the model. These findings suggest that strengthening integrated marketing strategies that emphasize both core and supporting factors is essential to enhance consumer purchase decisions. This study is expected to contribute practical insights for developing more effective marketing strategies for agribusiness MSMEs, particularly in rural contexts.